Multiculturalismo y capitalismo. Una lectura desde la sospecha - Gómez Martínez, Diego León (2023)
This article discusses multiculturalism from a critical hermeneutical perspective. This paper, which is descriptive and reflective, approaches multicultu ralism and pluralism conceptually. It supports the idea that multiculturalism is a strategic liberal doctrine that is used to help collective identities enter the market, strengthen the capitalist project, and ensure its hegemonic victory in consumer socie ty and the modern state.